Biogenic Amines on Food Safety - Ruiz-Capillas, Claudia (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Biogenic amines have been known for some time. These compounds are found in varying concentrations in a wide range of foods (fish, cheese, meat, wine, beer, vegetables, etc.) and their formations are influenced by different factors associated to those foods (composition, additives, ingredients, storage, microorganism, packaging, handing, conservation, etc.). The intake of foods containing high concentrations of biogenic amines can present a health hazard. Additionally, they have been used to establish indexes in various foods in order to signal the degree of freshness and/or deterioration of food. Nowadays, there has been an increase in the number of food poisoning episodes in consumers associated with the presence of these biogenic amines, mainly associated with histamines. Food safety is one of the main concerns of the consumer and safety agencies of different countries (EFSA, FDA, FSCJ, etc.), which have, as one of their main objectives, to control these biogenic amines, principally histamine, to assure a high level of food safety.Therefore, it is necessary to deepen our understanding of the formation, monitoring and reduction of biogenic amines during the development, processing and storage of food, even the effect of biogenic amines in consumers after digestion of foods with different levels of these compounds.With this aim, we are preparing a Special Issue on the topic of ""Biogenic Amines in Food Safety"", and we invite researchers to contribute original and unpublished research articles and reviews articles that involve studies of biogenic amines in food, which can provide an update to our knowledge of these compounds and their impacts on food quality and food safety.